3D fluid-structure interaction (FSI) simulation of new type vortex generators in smooth wavy fin-and-elliptical tube heat exchanger. Issue 8 (7th November 2016) - Lotfi, Babak; Sunden, Bengt; Wang, Qiu-Wang
Abstract : Purpose: The purpose of this paper is to investigate the numerical fluid-structure interaction (FSI) framework for the simulations of mechanical behavior of new vortex generators (VGs) in smooth wavy fin-and-elliptical tube (SWFET) heat exchanger using the ANSYS MFX Multi-field® solver. Design/methodology/approach: A three-dimensional FSI approach is proposed in this paper to provide better understanding of the performance of the VG structures in SWFET heat exchangers associated with the alloy material properties and geometric factors. The Reynolds-averaged Navier-Stokes equations with shear stress transport turbulence model are applied for modeling of the turbulent flow in SWFET heat exchanger and the linear elastic Cauchy-Navier model is solved for the structural von Mises stress and elastic strain analysis in the VGs region. Findings: Parametric studies conducted in the course of this research successfully identified illustrate that the maximum magnitude of von Mises stress and elastic strain occurs at the root of the VGs and depends on geometrical parameters and material types. These results reveal that the titanium alloy VGs shows a slightly higher strength and lower elastic strain compared to the aluminum alloy VGs. Originality/value: This paper is one of the first in the literature that provides original information mechanical behavior of a SWFET heat exchanger model with new VGs in the field of FSI coupling technique.